PENGARUH STRATEGI LRD DALAM MENINGKATKAN KETERAMPILAN MEMBACA BAHASA ARAB SISWA KELAS VII - Ainun Naim; Hasyim Fanirin; Dewi Utami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the impact of the Listen-Read-Discuss (LRD) strategy on improving Arabic reading skills among seventh-grade students of MTs Ma’had Al-Zaytun. The study was motivated by students’ low reading proficiency, often caused by teacher-centered and less interactive teaching methods. To address this issue, the LRD strategy was implemented to encourage more active student participation. This study employed a quantitative approach with a quasi-experimental design. A total of 52 students were selected as participants and divided equally into experimental and control groups, with the experimental group receiving instruction through the LRD strategy, while the control group received conventional teaching. Data were collected using pre-test and post-test instruments that had been validated and tested for reliability. The independent t-test results showed a significanca value of 0.000, indicating a significant difference between the experimental and control groups. The findings confirm that the LRD strategy effectively improves students’ Arabic reading skills. Therefore, this strategy is recommended for Arabic language learning as it promotes a more active, participatory, and interactive classroom environment.